A the Pengaruh analisis pengaruh judi online, pinjaman online, dan lingkungan pergaulan terhadap nilai akademi mahasiswa nilai akademik mahasiswa: Studi kasus mahasiswa fakultas ekonomi dan bisnis universitas Muhammadiyah Surakarta - Fahmi, Harun Alfahmi (Determinasi: Jurnal Penelitian Ekonomi Manajemen dan Akuntansi, 2024)
The perpose of this research is to obtain empirical evidence of the influence of online gambling, online loans and the social environment on academic grades among students at the Faculty of Economics and Business, Muhammadiyah University of Surakarta. This research was conducted by distributing questionnaires to respondents with the criteria being that they are students at the Faculty of Economics and Business, Muhammadiyah University of Surakarta and are interested in or have already invested in the capital market with the variables in this research, namely (1) Online Gambling (2) Online Loans (3) Social Environment (4) Student academic scores. The number of research respondents was 33 students and data management used SMRTPLS 4.0 with multiple regression analysis techniques. The results of this research state that online gambling and online loans do not affect the academic grades of students at the Faculty of Economics and Business, Muhammadiyah University of Surakarta.